2001
DOI: 10.1021/ja003135d
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Electroluminescent Poly(phenylene vinylene)s with Balanced Electron- and Hole Injections

Abstract: We report a new route for the design of efficient soluble electroluminescent PPV-based copolymers bearing electron-deficient oxadiazole (OXD) moieties on side chains. The introduction of OXD through a long alkylene spacer with PPV backbone provides a molecular dispersion of OXD in the film; both the side chain OXD and the main chain PPV do retain their own electron-transport and emissive properties, respectively. The use of phenylene vinylene derivatives with asymmetric and branched substituents and a long spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
161
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(166 citation statements)
references
References 57 publications
3
161
1
1
Order By: Relevance
“…It was observed that DI p vaules (the difference between anodic I pa and cathodic peak electric current I pc ) for the cyclic PVBCZ were larger than those of corresponding linear precursor, suggesting that the cyclic PVBCZ could have an efficient charge-transport site. [21] The electrochemical properties of cyclic PVBCZ is now being explored in detail.…”
mentioning
confidence: 99%
“…It was observed that DI p vaules (the difference between anodic I pa and cathodic peak electric current I pc ) for the cyclic PVBCZ were larger than those of corresponding linear precursor, suggesting that the cyclic PVBCZ could have an efficient charge-transport site. [21] The electrochemical properties of cyclic PVBCZ is now being explored in detail.…”
mentioning
confidence: 99%
“…This synthetic route is slightly different from the one that has been reported. 24 Specifically, in the present case, 4-hydroxybenzoic acid, the starting material, reacted with acetylchloride to afford the corresponding acetoxy derivative. Following the construction of the oxadiazole ring, the acetoxy group was hydrolyzed by acid catalyzed hydrolysis.…”
Section: Synthesis and Characterizationmentioning
confidence: 86%
“…The onset oxidation potential (E onset (ox)) is 1.48 V and onset reduction potential (E onset (red)) is −1.20 V. It is suggested that the copolymer containing iridium has better electron injection and transporting properties due to the incorporation of charged Ir complex into the copolymer. The HOMO and LUMO energy levels of the polymer materials can be calculated from the E onset (ox) and E onset (red), based on the reference energy level of ferrocene (4.8 eV below the vacuum level) [20,21] 2 Cl/PVK(1.0) is estimated to be about 5.88 eV, and LUMO level to be about 3.2 eV. As a result, it may be a good candidate as a electrophosphorescent material for application in PLED.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%